THEMATIC DEVELOPMENT OF READING TEXTS IN ENGLISH TEXT BOOKS FOR SENIOR HIGH SCHOOL STUDENTS GRADE XI - Aeningsih, Nur (ENCOUNTER, 2012)
In written communication, messages are realized through sentences. And in order to make our sentences easily be understood, we should consider the order of the words that construct them. The objective of this study is to describe the thematic development of reading texts found in three English textbooks for senior high school students grade XI (âLook Aheadâ, âEnglish Zoneâ and âEnglish Aliveâ) and the pattern applied. The corpus is selected from the number of reading texts representing genres exist there. Applying Egginsâs (1994) thematic organization the study reveals significant differences in type of thematic development used in those three books. The study concludes that book writers should be conscious of these tools in order to use them effectively and create more cohesive texts. Based on the result, some suggestion are proposed to English teachers, book writer and publishers.